Effect Of Grain Refinement Process Using Equal Channel Angular Pressing On The Properties And Corrosion Behaviour Of Sn-3.0ag-0.5Cu Solder - Abu Bakar, Nur Adriana Nazifa (2019)
Due to the inherent toxicity of Pb, environmental regulations have been enforced to eliminate the usage of Pb-based solders in electronic devices. Sn-Ag-Cu alloys is an attractive candidate due to good mechanical properties, good wettability and low melting temperature. However, the reliability of SAC solders is still a serious concern especially under long term exposure to heat or in corrosive environment. There is potential to improve the corrosion behavior and increase solder joint reliability by using Equal Channel Angular Pressing (ECAP) as a grain refinement process. The aim of this project was to evaluate the microstructure, mechanical properties and corrosion behavior of SAC305 alloy subjected to ECAP up to 4 passes. In this study, the mechanical properties showed that the 4 passes ECAPed SAC305 alloy exhibited the highest hardness value (17.5 HV) with improvement of shear strength (70.5 MPa). ECAP was used to alter the microstructure of SAC305 alloy by reducing the large Sn dendrites into fine and equiaxed grains (5.51 μm). ECAP also was observed to result in smaller IMC particles and better distribution of them in the Sn matrix. It also showed the smallest crystallite size (0.28 μm) and the highest lattice strain (4.36X10-1). ECAP process resulted in improved wettability based on largest spreading area and smallest wetting angle compared to the others. As a result of grain refinement and more evenly distributed IMCs, solder had higher hardness after ECAP. The corrosion resistance was also improved based on lowest weight loss, lowest corrosion rate and more positive value of corrosion potential. The morphology on surface of immersion test samples showed rounded shape particles and then was replaced with root-like film. ECAP 4 passes sample after potentiodynamic polarization was uniformly covered with plate-like shape corrosion product while the other samples suffered from selective corrosion with evidence of pits on the surface. Phase and elemental analyses revealed the formation of several corrosion product such as SnO2, SnCl2 and Sn3O(OH)2Cl2 on the surface. The increase number of passes can induced grain refinement in SAC305 samples with better mechanical properties, wettability behavior and corrosion resistance.